Two families of pseudo metacirculants - Cui, Li (Ars mathematica contemporanea, 2022)
A split weak metacirculant which is not metacirculant is simply called a pseudo metacirculant. In this paper, two infinite families of pseudo metacirculants are constructed.
Keywords: metacikličen; metacirculant; metacirkulant; metacyclic; razcepljen šibki metacirkulant; split weak metacirculant